You are on page 1of 2

Funcion original

t = -10:0.01:10;
y = exp(-abs(t).^4).*(heaviside(t) - heaviside(t - 4));
y1 = exp(-abs(2*t).^4).*(heaviside(2*t) - heaviside(2*t - 4));
y2 = exp(-abs(t + 2).^4).*(heaviside(t + 2) - heaviside(t - 2));
y3 = exp(-abs(2 - 2*t).^4).*(heaviside(2 - 2*t) - heaviside(2 - 2*t - 4));

Funcion(1)

figure;
subplot(4,1,1);
plot(t, y);
xlabel('t');
ylabel('y(t)');
title('y(t)');

subplot(4,1,2);
plot(t, y1);
xlabel('t');
ylabel('y1(t)');
title('y1(t) = y(2t)');

Funcion(2)

subplot(4,1,3);
plot(t, y2);
xlabel('t');
ylabel('y2(t)');
title('y2(t) = y(t + 2)');

Funcion(3)

subplot(4,1,4);
plot(t, y3);
xlabel('t');
ylabel('y3(t)');
title('y3(t) = y(2 - 2t)');

1
2

You might also like